Study of structural and luminescence properties of lead lithium borophosphate glass system doped with Ti Ions - T.Q., Leow; P.M., Leong; T.Y., Eeu; Ibrahim, Z.; Hussin, R. (Universiti Kebangsaan Malaysia, 2014)
Study of a series of lead lithium borophosphate glass samples was performed to determine the structural and luminescence properties. The glass samples containing the composition of 20PbO-xLi2O-30B2O3-(50-x)P2O5-2TiO2 (where x = 0, 5, 10, 15, 20) system were prepared using melt-quenching technique. The PbO-Li2O-B2O3-P2O5-TiO2 samples were investigated for structural properties using Fourier transform infrared and photoluminescence spectroscopy for studies of luminescence properties. The results from FT-IR showed the presence of trigonal and tetrahedral PO4, PO3, BO4 and BO3 groups within the host network structure. The samples exhibit luminescence emission centered at 420, 482 and 496 nm when excited at 300 nm wavelength. The emission peak at 420 nm were assigned to F center emission and charge-transfer transition of Ti4+ ions. The results showed that emission intensity was dependent on lithium contents in Ti-doped lead lithium borophosphate glass composition.